ChiCaRo: tele-presence robot for interacting with babies and toddlers‡. (16th February 2018) - Abe, Kasumi; Shiomi, Masahiro; Pei, Yachao; Zhang, Tingyi; Ikeda, Narumitsu; Nagai, Takayuki
Abstract: The progress of super-aging societies is decreasing opportunities for interaction between grandparents and grandchildren due to increased nuclear families. This paper reports a tele-presence robot named ChiCaRo, which is designed to promote interaction with babies/toddlers and encourage remote communication between grandparents and grandchildren. We experimentally investigated ChiCaRo's social acceptance with 17 adults and 19 children in a play room environment. The adult participants evaluated ChiCaRo highly in the context of remote interaction with their children. Next, we conducted field trials in real-home environments with three nuclear families and their grandparents who operated ChiCaRo to investigate its effectiveness. After one-week field trials, the grandparents reported that ChiCaRo encouraged both interaction with their grandchildren and supplemented childcare, e.g. watching babies/toddlers instead of their parents. Abstract :